2013
DOI: 10.1038/nmeth.2543
|View full text |Cite
|
Sign up to set email alerts
|

TALE-mediated modulation of transcriptional enhancers in vivo

Abstract: We tested whether Transcription Activator-Like Effectors (TALEs) can mediate repression and activation of endogenous enhancers in the Drosophila genome. TALE-repressors (TALERs) targeting each of the five even-skipped (eve) “stripe” enhancers generated repression specifically of the focal stripes. TALE-activators (TALEAs) targeting the eve promoter or eve enhancers caused increased expression primarily in cells normally activated by the promoter or targeted enhancer, respectfully. The phenotypic effects of TAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…While the resulting changes in expression, particularly in case of our TALE-VP64 transcription factor, were modest, our results mark a significant extension from the previously reported epigenomic editing of Drosophila enhancers located within 10kb from their target genes(Crocker and Stern, 2013). We predict that the molecular toolbox for future treatments of cognitive and psychiatric disease will include targeted editing of long-range enhancer elements regulating gene expression critical for neuronal plasticity and behavior.…”
Section: Discussionsupporting
confidence: 60%
“…While the resulting changes in expression, particularly in case of our TALE-VP64 transcription factor, were modest, our results mark a significant extension from the previously reported epigenomic editing of Drosophila enhancers located within 10kb from their target genes(Crocker and Stern, 2013). We predict that the molecular toolbox for future treatments of cognitive and psychiatric disease will include targeted editing of long-range enhancer elements regulating gene expression critical for neuronal plasticity and behavior.…”
Section: Discussionsupporting
confidence: 60%
“…TALE repressors have been used to successfully suppress multiple endogenous genes in human cells (82), model organisms (83), and plants (84). In addition to targeting endogenous genes, TALE repressors are valuable tools for the development of synthetic gene circuits (21, 22).…”
Section: Synthetic Repressorsmentioning
confidence: 99%
“…In the case of Cas9, the catalytically inactive mutant form of Cas9 (referred to as dCas9 [40]), which contained two mutations of the RuvC1 and HNH nuclease domains can be used for RNA-mediated custom-designed transcriptional factors. Currently, gene fusions of TALEs/dCas9 to several types of activation/repression domains are available for gene regulation tools in many organisms including mammalians and plants [64][65][66]. Piatek et al [67] demonstrated the target-specific gene regulation using dCas9-based transcriptional activator and repressor in tobacco.…”
Section: Molecular Breeding: Genomics and Genetic Engineering In Woodmentioning
confidence: 99%